2005
DOI: 10.1248/bpb.28.224
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic-Like Properties of the Chloroform Extract of Maytenus obtusifolia MART. Roots

Abstract: The species of Maytenus (Celastraceae) are effectives against several kind of sickness including cancer, gastric ulcers, dyspepsia and also useful as an antibacterial and antiinflammatory.1-3) Sesquiterpenes, triterpenes, quinone-methide and sesquiterpene pyridine alkaloids have been identified in these species. 1,4) Maytenus obtusifolia MART. is a plant found in many states of the Northeast and South-east of Brazil, which is used in traditional medicine for the treatment of ulcer.5) A chemical study of chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(6 reference statements)
0
12
0
1
Order By: Relevance
“…28 When compared to doses of 200 400, 600 and 800 mg/kg of Maytenus macrocarpa, it didn't show a statistically significant difference, revealing a potential neuroleptic effect. In contrast, a study of Maytenus obtusifolia MART root, demonstrated antipsychotic effect in the experimental model of catalepsy, 10 therefore, this study expanded the evidence of the neuroleptic activity to the macrocarpa species, more precisely, the bark. This antipsychotic effect could be explained with the secondary metabolites of the genus Maytenus.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…28 When compared to doses of 200 400, 600 and 800 mg/kg of Maytenus macrocarpa, it didn't show a statistically significant difference, revealing a potential neuroleptic effect. In contrast, a study of Maytenus obtusifolia MART root, demonstrated antipsychotic effect in the experimental model of catalepsy, 10 therefore, this study expanded the evidence of the neuroleptic activity to the macrocarpa species, more precisely, the bark. This antipsychotic effect could be explained with the secondary metabolites of the genus Maytenus.…”
Section: Discussionmentioning
confidence: 79%
“…7 Other species of genus Maytenus, for example M. aquifolium, M. robusta and M. obtusifolia MART have shown antiulcer activity. [8][9][10] In Maytenus ilicifolia, acute diuretic activity and hipotensive activity were found, 11 as well as antiprotozoal activity which was attributed to quinonemethide triterpenes. 12 Furthermore, particular effects upon thecentral nervous system have been registered.M.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is endemically encountered in "campo rupestre" (Rupiculous field grasslands) regions mainly in Bahia and Minas Gerais States of Brazil (Okano, 1992). Antiulcerogenic and analgesic effects (Queiroga et al, 2000;Gonzalez et al, 2001;Santos et al, 2007;Mota et al, 2008), antitumoral (Pullen et al, 2003;Ravelo et al, 2004), antimicrobial activity (Orabi et al, 2001;Estevam et al, 2009), antispasmodic (El Tahir et al, 1999, insecticidal (Avilla et al, 2000), citotoxic (Spivey et al, 2002), neuroleptic and anticonvulsant properties (Sousa & Almeida, 2005;Quintans-Júnior et al, 2008), antiinflammatory (Jorge et al, 2004;Santos et al, 2007;), antiespermatogenic (Montanari et al, 1998) and antidiabetical properties (Okine et al, 2005) are pharmacological activities attributed to different species of Maytenus.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical screening showed the occurrence of three different chemical classes of secondary metabolites in M. obtusifolia, alkaloids for example N-methylfl indersine, pentacyclic triterpenes as 3,4-secofriedelan-3-oic acid, 3b-hydroxy-11, 13-en-oleanane, 7-oxofriedelin, 3-oxo-29-hydroxyfriedelan, friedelin, 3b-hydroxy-9, 12-enoleanane and 3b-hydroxy-9,12-en-ursane and fl avonoids of the type 4'-O-methyl-(-)-epigallocatechin, ourateaproanthocyanidin A, catechin and epicatechin (Silva et al, 2008). Pharmacological studies demonstrated that this species possess analgesic (Freire, 1998) and neuroleptic activities (De Sousa & De Almeida, 2005).…”
Section: Introductionmentioning
confidence: 99%